Early-life exposure to mycotoxin zearalenone exacerbates aberrant immune response, oxidative stress, and mortality of Caenorhabditis elegans under pathogen Bacillus thuringiensis infection - Chun Ming How; Yong-Shan Li; Wei-Yun Huang; Chia-Cheng Wei (Ecotoxicology and Environmental Safety, 2024)
Zearalenone (ZEN) is a prevalent mycotoxin that severely impacts human and animal health. However, the possible interactions between ZEN exposure, pathogen infection, immune system, and reactive oxygen species (ROS) were rarely investigated. We studied the effects of early-life ZEN (50 µM) exposure on the immune response of Caenorhabditis elegans against Bacillus thuringiensis infection and the associated mechanisms. The transcriptomic responses of C. elegans after early-life ZEN exposure were investigated using RNA sequencing and followed by verification using quantitative PCR analysis. We also investigated the immune responses of the worms through B. thuringiensis killing assays and by measuring oxidative stress. The transcriptomics result showed that early-life exposure to ZEN resulted in 44 differentially expressed genes, 7 of which were protein-coding genes with unknown functions. The Gene Ontology analysis suggested that metabolic processes and immune response were among the most significantly enriched biological processes, and the KEGG analysis suggested that lysosomes and metabolic pathways were the most significantly enriched pathways. The ZEN-exposed worms exhibited significantly reduced survival after 24-h B. thuringiensis infection, reaching near 100% mortality compared to 60% of the controls. Using qRT-PCR assay, we found that ZEN further enhanced the expression of immunity genes lys-6, spp-1, and clec-60 after B. thuringiensis infection. A concurrently enhanced ROS accumulation was also observed for ZEN-exposed worms after B. thuringiensis infection, which was 1.2-fold compared with the controls. Moreover, ZEN exposure further enhanced mRNA expression of catalases (ctl-1 and ctl-2) and increased catalase protein activity after B. thuringiensis exposure compared with their non-exposed counterparts, suggesting an elevated oxidative stress. This study suggests that early-life exposure to mycotoxin zearalenone overstimulates immune responses involving spp-17, clec-52, and clec-56, resulting in excessive ROS production, enhanced oxidative stress as indicated by aggravated ctl expression and activity, and a decline in host resistance to pathogenic infection which ultimately leads to increased mortality under B. thuringiensis infection. Our findings provide evidence that could improve our understanding on the potential interactions between mycotoxin zearalenone and pathogens.